PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA, KEADILAN PROSEDURAL TERHADAP KINERJA KARYAWAN DENGAN VARIABEL MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Ely Kartikaningdyah; Nurul Kameliza Utami (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
The purpose of this study is to find out whether there is influence of transformational leadership, job satisfaction, procedural fairness to employee performance with moderation variable that is Organizational Citizenship Behavior (OCB). Source of data is primer using the questionnaire taken on the object of research of Bank Syariah Batam with the number of samples as much as 150 respondents of Bank Syariah employees. The research used quantitative descriptive analysis and processed data with SPSS 22 that is regression analysis and path analysis. The results show that there is a positive influence of transformational leadership, job satisfaction, procedural justice on employee performance. Transformational leadership, job satisfaction affects OCB, but procedural justice has no effect on OCB. OCB mediates transformational leadership on employee performance, OCB also mediates job satisfaction on employee performance, but OCB does not mediate procedural justice